2019
DOI: 10.1017/ice.2019.270
|View full text |Cite
|
Sign up to set email alerts
|

Errors in antibiotic transitions between hospital and nursing home: How often do they occur?

Abstract: We performed systematic review on 40 paired hospital and nursing home charts from a clinical trial to evaluate the fidelity of transitions of care among those discharged on antibiotics. We found that 30% of transitions included an inappropriate change to the patient’s antibiotic plan of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…41,42 Given reduced antibiotic stewardship oversight, poor discharge documentation, and frequent empirical and broad-spectrum prescribing practices, antibiotic prescribing on discharge to NH is associated with adverse events, including rehospitalization and CDI. [41][42][43][44] Alongside the large proportion of patients receiving a hospitalassociated prescriptions, nearly one-fifth of enrolled patients received an NH-associated prescription for a new indication during their NH stay, predominantly for UTIs. Previous research demonstrated that NH antibiotic prescribing is often inappropriate, with some estimates surpassing 50%, particularly due to inappropriate urine culturing and treatment of asymptomatic bacteriuria.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Given reduced antibiotic stewardship oversight, poor discharge documentation, and frequent empirical and broad-spectrum prescribing practices, antibiotic prescribing on discharge to NH is associated with adverse events, including rehospitalization and CDI. [41][42][43][44] Alongside the large proportion of patients receiving a hospitalassociated prescriptions, nearly one-fifth of enrolled patients received an NH-associated prescription for a new indication during their NH stay, predominantly for UTIs. Previous research demonstrated that NH antibiotic prescribing is often inappropriate, with some estimates surpassing 50%, particularly due to inappropriate urine culturing and treatment of asymptomatic bacteriuria.…”
Section: Discussionmentioning
confidence: 99%
“…Sparked by the identification of opportunities for improved prescribing in this setting, applications of similar strategies during transitions of care have arisen more recently. In a 2019 systematic review of 40 paired hospital and nursing home sites, Dickinson and colleagues reported that approximately 30% of transitions involved an inappropriate change to the antibiotic plan of care, thus establishing a significant area ripe for improvement [ 26 ]. With increasing recognition for its value, preliminary studies assessing stewardship services at transitions of care have illustrated promising results.…”
Section: Stewardship Foundationsmentioning
confidence: 99%
“…auf weniger breitwirksame Therapie bei Ausschluss eines entsprechend resistenten Erregers, Dosis und Dauer sind in vielen Krankenhausabteilungen Optimierungsbereiche identifizierbar. Dies gilt auch für Empfehlungen zur Weiterführung von Therapien bei Entlassungein Bereich, der bisher noch zu wenig Beachtung gefunden hat [21].…”
Section: Merkeunclassified